Biodiversity of transitional waters: species composition and comparative analysis of hard bottom communities from the south-eastern Italian coast. (February 2014) - Cardone, Frine; Corriero, Giuseppe; Fianchini, Alessandra; Gravina, Maria Flavia; Nonnis Marzano, Carlotta
<x content-type="archive" xml:space="preserve">Abstract</x> Numerous studies have focused on the soft bottom macrozoobenthos from Mediterranean transitional environments, pointing out a correlation between the variation in environmental parameters and changes occurring in benthic communities. Less attention has been paid to the study of hard bottom organisms settling on both natural and artificial substrates usually present within the basins and often constituting peculiar communities. The ecological role of such communities is remarkable, since they often reach high values of species richness and include bioconstructor organisms able to build true reefs. These reefs can strongly impact the environment, improving biodiversity through the increase of spatial heterogeneity. The present work aims to supplement new faunistic data on five lagoon systems of the south-eastern Italian coast, integrating the still fragmentary knowledge of their macrozoobenthos through the study of hard substrate communities. Sampling was performed on hard substrates colonized by complex benthic communities. The assemblages recorded were then compared in the light of the study sites' main ecological traits. Our data highlighted the occurrence of a rich benthic macrofauna, with 100 taxa found. This markedly increases the value of species richness reported in the literature for the macrozoobenthos of the study sites. In particular, the species list provided for the Ugento Basins was the first ever compiled for this site. In spite of their geographical proximity, the investigated sites, according to their diverse environmental conditions, showed substantial differences as regards their respective macrozoobenthic communities.